2021
DOI: 10.3389/fphar.2020.601887
|View full text |Cite
|
Sign up to set email alerts
|

In Silico, In Vitro and In Vivo Pharmacodynamic Characterization of Novel Analgesic Drug Candidate Somatostatin SST4 Receptor Agonists

Abstract: Background: Somatostatin released from the capsaicin-sensitive sensory nerves mediates analgesic and anti-inflammatory effects via its receptor subtype 4 (SST4) without influencing endocrine functions. Therefore, SST4 is considered to be a novel target for drug development in pain, especially chronic neuropathy which is a great unmet medical need.Purpose and Experimental Approach: Here, we examined the in silico binding, SST4-linked G protein activation and β-arrestin activation on stable SST4 expressing cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…MUC1 is anomalously expressed in numerous cancers. The coding production of MUC1 gene was a tumor marker for the diagnosis of thyroid cancer [ 14 , 15 ]. MUC1 expression is reported to be an important molecular marker of cervical squamous cell carcinoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 is anomalously expressed in numerous cancers. The coding production of MUC1 gene was a tumor marker for the diagnosis of thyroid cancer [ 14 , 15 ]. MUC1 expression is reported to be an important molecular marker of cervical squamous cell carcinoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin was released from nerve endings of isolated murine skin upon application of sodium polysulfide due to the activation of TRPA1 ion channels [6]. Somatostatin enters the systemic circulation and exerts analgesic and anti-inflammatory effects via sst4 receptors [32]. Our earlier data indicated that a reduction in vascular inflammation by DMTS was mediated by sst4 activation, but not by TRPA1 activation [25].…”
Section: Discussionmentioning
confidence: 98%
“…The experimental determination of the atomic resolution structure of SSTR4 has not been accomplished yet (Introduction). Homology modelling is an alternative method of choice [40,41,48,[51][52][53]61,62] for producing SSTR structures. Building a good SSTR model necessitates the selection of a template protein of good sequential agreement with the receptor.…”
Section: The Structure Of Sstr4mentioning
confidence: 99%